What Darwin never knew [videorecording (DVD)] - Rubin, John (John Michael); Holt, Sarah; DeNooyer, Rushmore; Davies, Serena; Carroll, Sean B.; Carroll, Sean B. (Distributed by PBS Distribution, 2010)
The source of the earth's great variety of animals was a scientific mystery until Charles Darwin proposed the idea of natural selection. Nova presents breakthroughs in a new science nicknamed "evo devo" that are linking the enigma of origins to another of nature's mysteries, the development of embryos.